2010
DOI: 10.1109/tifs.2009.2038751
|View full text |Cite
|
Sign up to set email alerts
|

Face Verification Across Age Progression Using Discriminative Methods

Abstract: Abstract-Face verification in the presence of age progression is an important problem that has not been widely addressed.In this paper, we study the problem by designing and evaluating discriminative approaches. These directly tackle verification tasks without explicit age modeling, which is a hard problem by itself. First, we find that the gradient orientation (GO), after discarding magnitude information, provides a simple but effective representation for this problem. This representation is further improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(13 citation statements)
references
References 42 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…They measured drift coherency in both children and adults and presented promising preliminary results. Ling et al [11] used discriminant image descriptors based on Gradient Orientation Pyramids (GOP). They found that GOP representation combined with SVM classification is more invariant to aging effects compared to other methods, and that the difficulty involved in face verification saturates for age gaps between 4 years and 10 years.…”
Section: Discriminative Methodsmentioning
confidence: 99%
“…They measured drift coherency in both children and adults and presented promising preliminary results. Ling et al [11] used discriminant image descriptors based on Gradient Orientation Pyramids (GOP). They found that GOP representation combined with SVM classification is more invariant to aging effects compared to other methods, and that the difficulty involved in face verification saturates for age gaps between 4 years and 10 years.…”
Section: Discriminative Methodsmentioning
confidence: 99%
“…To eliminate illumination, effect efficient preprocessing technique used in [16]. Gabor wavelet based feature extraction [17] is employed in effective face recognition but size of feature vector was obtained being large delays effective computation.…”
Section: Literature Surveymentioning
confidence: 99%
“…The left and right eye, left and right nose, mouth were the features. Ling et al (2010) have implemented a discriminative approach to capture the face features, Support Vector Machine (SVM) and Gradient Orientation Pyramid (GOP) to be applied for face recognition. The quality of photos, glass appearance, facial hair changes were taken as the features of age recognition.…”
Section: Jcsmentioning
confidence: 99%
“…Ichikawa et al (2008) have implemented the usage of decision tree C4.3 algorithm, to classify the occluded and non occluded part of the facial image. Ling et al (2010) have discussed a discriminative approach to fully capture the face features, Support Vector Machine (SVM) and Gradient Orientation Pyramid (GOP) to be applied for face Science Publications…”
Section: Introductionmentioning
confidence: 99%